SOLID WASTE MANAGEMENT OF STREET VENDING ACTIVITIES IN MALIOBORO AREA, YOGYAKARTA - , Mira Ekawati, Dr. Alberto Gianoli ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study focus on the solid wastes management of street vending activities in Malioboro area Yogyakarta by seeing how is the main characteristic of existing solid waste management related to street vending activities, the roles of different stakeholder in waste management, and the constraints of sustainable waste management practices from political, institutional, financial, social, technical and economical aspect. The objective of this research is to identify the current waste management system of street vending activities in Malioboro area in term of how the system elements are working and how the actors of waste management system play important roles to support the system and to figure out the challenges that are exists sustainable management practices. The methodology of this research is exploratory for single embedded case study. The data is collecting by survey with quantitative and qualitative approach using questionnaires and depth interview. The research is conducted through observation and descriptive analysis toward the result of direct observation, desk study and data analysis. The respondent of this study are the street vendors, the visitors, the local government and street vendor association and non government organization. The sample is selected by purposive random sampling during the field work by asking the respondents from different groups as mentioned above. The data analysis for quantitative data is doing by descriptive test to know the frequencies and relation between two variables. The data analysis for the qualitative data is by coding, grouping and highlighting critical themes based on the main theories. Street vending waste management in Malioboro area consist of several elements which are waste generation, collection, transfer, transport and final disposal. The waste generation is relating the existing of waste in the source. Street vending waste in Malioboro is dominated by food waste and plastic waste. Most vendors stored their waste in the waste bins without segregate organic and inorganic waste. Waste collection method is door to door service using push chart and accumulate in temporarily waste disposal site in Pringgokusuman and Pasar Kembang. The wastes then being transported using dump truck, special vehicles for waste, with in 19 km distance to final site disposal in Piyungan, Bantul regency. The stakeholders of street vending waste management are the street vendors, the visitors, the local government, street vendor association and non government organization. Street vendor play roles as service users who pay the tariff, provide waste bin, obey the rules. Visitors play roles as social controller and give opinion regarding the quality of the service. The local government play roles as regulatory bodies that make the policy, set the amount of tariff, provide the facilities, and raise community awareness and doing monitoring and control. Street vending association plays roles as communicator and representative of the member for decision making process in the city level. Politically, the city regulation on waste management and street vending management have not address the issue of reduce, reuse and recycle in waste management system as it is mandatory by National Act No 9/2008.Institutionally, the decentralization process on waste management in Malioboro area do not successfully meet the objective as it was mandatory by Mayor Yogyakarta Act on the function of Oneâs stop office of Malioboro due to lack of staff, facilities and fund. Technically, street vending waste management in Malioboro constraints refer to lack of waste bin, lack of temporarily waste disposal sites which cannot accommodate the volume of waste, lack of workers to collect the waste and lack of vehicle to transport the waste. Socially, the street vendors, visitors and local government considered the quality of waste management service in Malioboro is less good and need to be improved. Another challenge is misbehave of people on cause damage on the facilities and the habit of dumping or littering. Waste management in Malioboro is economically affected socio economic of the area by making street vending activities growth time to time and from street vending business they get income every day. To improve the system, the regulation on street vending management should be revised by addressing reduce, reuse, recycle principles. The adoption of curb collection method to collect the waste is more preferable to replace the door to door collection method.